NATURAL VARIATION IN EPIGENETIC GENE REGULATION AND ITS EFFECTS ON PLANT DEVELOPMENTAL TRAITS. (1st March 2014) - Turck, Franziska; Coupland, George
Abstract: In plants, epigenetic variation contributes to phenotypic differences in developmental traits. At the mechanistic level, this variation is conferred by DNA methylation and histone modifications. We describe several examples in which changes in gene expression caused by variation in DNA methylation lead to alterations in plant development. In these examples, the presence of repeated sequences or transposons within the promoters of the affected genes are associated with DNA methylation and gene inactivation. Small interfering RNAs expressed from these sequences recruit DNA methylation to the gene. Some of these methylated alleles are unstable giving rise to revertant sectors during mitosis and to progeny in which the methylated state is lost. However, others are stable for many generations and persist through speciation. These examples indicate that although DNA methylation influences gene expression, this is frequently dependent on classical changes to DNA sequence such as transposon insertions. By contrast, forms of histone methylation cause repression of gene expression that is stably inherited through mitosis but that can also be erased over time or during meiosis. A striking example involves the induction of flowering by exposure to low winter temperatures in Arabidopsis thaliana and its relatives. Histone methylation participates in repression of expression of an inhibitor of flowering during cold. In annual, semelparous species such as A. thaliana, this histone methylation is stably inherited through mitosis after return from cold to warm temperatures allowing the plant to flower continuously during spring and summer until it senesces. However, in perennial, iteroparous relatives the histone modification rapidly disappears when temperatures rise, allowing expression of the floral inhibitor to increase and limiting flowering to a short interval. In this case, epigenetic histone modifications control a key adaptive trait, and their pattern changes rapidly during evolution associated with life‐history strategy. We discuss these examples of epigenetic developmental traits with emphasis on the underlying mechanisms, their stability, and adaptive value.